2016
DOI: 10.1186/s12912-016-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

High use of over-the-counter analgesic; possible warnings of reduced quality of life in adolescents - a qualitative study

Abstract: BackgroundUse of over-the-counter analgesics among adolescents has increased markedly. High consumption of over-the-counter analgesics among adolescents is associated with frequent pain, lower self-esteem, reduced sleep, lower educational ambition, binge drinking, higher caffeine consumption, and part-time employment. Knowledge about life experiences of adolescents who frequently use over-the-counter analgesics may be useful to prevent health problems. The purpose of the study was to increase knowledge about a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 50 publications
0
27
0
Order By: Relevance
“…Neither Skarstein et al () nor Albatti et al () found gender or social differences regarding use of OTCAs. This was surprising when pain is found to be more common among girls (Haraldstad et al, ).…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Neither Skarstein et al () nor Albatti et al () found gender or social differences regarding use of OTCAs. This was surprising when pain is found to be more common among girls (Haraldstad et al, ).…”
Section: Resultsmentioning
confidence: 91%
“…(Holmström et al, ) She also notes that mothers are usually the one who commit to resolve their youths pain problems. Further mothers were most likely to recommend the use of OTCAs (Skarstein et al, ). In line with Chambers, Reid, McGrath, and Finley (), Skarstein also found that the adolescents became more independent in their use of OTCAs with increasing age (Chambers et al, ; Skarstein et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…3; medicines with them, while others reported that they did not need information because they knew the medicines well, from their prior use. This familiarity also seems connected to the frequency of minor ailments: it should be investigated if this attitude toward the use of OTC drugs is due to the pain (Lagerløv, Rosvold, Holager, & Helseth, 2016;Skarstein et al, 2016) or to the perceived safety of these drugs. Indeed, given the familiarity with the OTC medicines, the teenagers seem to underestimate the risks related to misuse.…”
Section: Discussionmentioning
confidence: 99%
“…Teenagers consider significant the feeling of being appreciated by their peers (Skarstein et al, 2016): having positive relationships with friends contributes to their self-esteem and social position. With reference to health-related information-seeking and decision-making behaviors, it was observed that, for instance, girls ask each other for advice about effective relief of dysmenorrhea (Skarstein et al, 2016). Therefore, friends, too, can contribute to teenagers' health behavior and their influence is investigated in this study.…”
Section: The Influence Of the Social Groupsmentioning
confidence: 99%
See 1 more Smart Citation